Mesophication in temperate Europe: A dendrochronological reconstruction of tree succession and fires in a mixed deciduous stand in Białowieża Forest - Andreea P. Spînu (Wiley, 2020)
Abstract The shift from shade‐intolerant species to shade‐tolerant mesophytic species in deciduous and mixed forests of the temperate zone is well described in studies from North America. This process has been termed mesophication and it has been linked to changes in fire regime. Fire suppression results in the cessation of establishment of heliophytic, fire‐dependent tree species such as oak (Quercus) and pine (Pinus). Due to the scarcity of old‐growth forests in Europe, data on long‐term compositional changes in mixed forests are very limited, as is the number of studies exploring whether fire played a role in shaping the dynamics. The aim of this study was to reconstruct tree succession in a 43‐ha natural mixed deciduous forest stand in Białowieża Forest (BF), Poland using dendrochronological methods. In addition, the presence of aboveground fire legacies (charred and fire‐scarred deadwood) enabled the fire history reconstruction. Dendrochronological data revealed tree establishment (Quercus) back to the end of the 1500s and fires back to 1659. Under a regime of frequent fires until the end of the 18th century, only oak and pine regenerated, sporadically. A shift in the fire regime in the first half of the 19th century triggered oak and pine cohort regeneration, then gradually spruce (Picea) encroached. Under an increasingly dense canopy and less flammable conditions, regeneration of shade‐tolerant Carpinus, Tilia, and Acer began simultaneously with the cessation of oak and pine recruitment. Synthesis. The study reports the first evidence of mesophication in temperate Europe and proves that fire was involved in shaping the long‐term dynamics of mixed deciduous forest ecosystems. Our data suggest that fire exclusion promoted a gradual recruitment of fire‐sensitive, shade‐tolerant species that inhibited the regeneration of oak and pine in BF.